Dose-finding trials in oncology - Ivanova, Anastasia (Henry Stewart Talks, 2007)
Maximum tolerable dose, Standard or 3+3 design, A+B designs, Phase I trials that use toxicity grades, Escalation versus fixed sample size designs for dose-finding trials, Continual reassessment method, Cumulative cohort design, Start-up rule, Design modifications for delayed toxicity outcomes, Trials with two agents and ordered groups
Archived at 2018/05/31